Opportunities for olive oil value chain enhancement through the by-products valorisation: A life cycle assessment in the Andalusian region (Spain) - Fernández-Lobato, Lázuli; Guido-Toledo, Juan Luis; Fendri, Mahdi; Vera, David (My University, 2020)
This work presents a Life Cycle Assessment (LCA) of the production of virgin olive oil in the most representative region of Spain (Jaen). The total cultivation area of Jaen is around 620,000 ha, where 580,000 ha are dedicated to olive grove. The scope is "from cradle to gate" in a study period of 5 harvests (2015-2020). The results obtained show a value for GHG emissions from 1.93 to 3.00 kg of CO2 equivalent, with a weighted average of 2.39 kg of CO2 equivalent per functional unit (1 kg of virgin olive oil).
Keywords: Cambios climáticos; Aceite de oliva - Industria; Impacto ambiental; Eco-design; Life cycle assessment; Olive oil production; Environmental impacts; Climate change